Implementation of Indonesian National Qualification Framework Based Curriculum in Higher Islamic Education - Ahid, Nur; Chamid, Nur (Jurnal Pendidikan Islam, 2021)
The era of globalization requires various sectors to make changes, including in the world of education. In higher education, the curriculum should be designed to comply with the Indonesian National Qualifications Framework (KKNI) to respond these changes. The curriculum is based on the framework of qualification levels which equalize, juxtapose, and unify learning outcomes with work experience into the types, forms and levels of higher education. This study aims to describe the implementation KKNI based curriculum for postgraduate program at the State Islamic Religious Institutions (PTKIN) in East Java. It applied descriptive-qualitative. The data were collected using observation, interview, and documentation techniques. The data were analysed using descriptive-qualitative analysis. The results shown that the implementation of KKNI based curriculum in postgraduate at PTKIN institutions in East Java took place from 2016 to 2020. The implementation began with socialization in the form of curriculum workshops. In those workshops, a curriculum draft and guidelines for its implementation were prepared. However, there were some in the implementation. One of them is that most of the lecturers did not understand the basic concepts of curriculum. To overcome this, intensive workshops were held to prepare syllabus, semester program plans and courses for each semester.